Comparison of physiological responses to six minute walk test and incremental shuttle walk test among COPD patients in UKMMC - R. Ayiesah,; Y. Y. Chang, (Universiti Kebangsaan Malaysia, 2010)
The objective of the study was to compare the physiological responses among COPD patient to Six Minute Walk Test (6MWT) and Incremental Shuttle Walk Test (ISWT). Twenty subjects were recruited for both 6MWT and ISWT that was carried out randomly. The readings of oxygen saturation (SpO2 ), heart rate (HR) and Modified Borg’s Score (MBS) were being taken before, during (each minute) and after each test. There were no significant difference observed in the peak HR and MBS between 6MWT and ISWT. There was no significant difference observed in the end SpO2 after both tests. In the two tests, HR and MBS increased linearly and were proportionate with time. However, our results showed that the distance walked in both test were significantly different and strongly related with more distance covered in 6MWT, with p < 0.05 (p = 0.01) and R = 0.58. Both 6MWT and ISWT elicited similar peak HRs and MBS suggesting both tests could be used to challenge patient to certain levels of cardiovascular and respiratory stress. There was no significant difference found in this study between the two tests. The two field tests could produce similar physiological responses in COPD patient.